Histopathological diagnoses revealed by indication-based renal allograft biopsies: a retrospective analysis - Eren, Eryigit; Tokac, Mehmet; Aydın, Alaaddin; Şahin, Taylan; Uslu, Hikmet Bora; Alkan, Selman; Dinçkan, Ayhan (The European Research Journal, 2023)
Objectives: Although there have been several advances in post-solid organ transplantation immunosuppression medications over the last two decades, the long-term survival of renal allografts did not significantly improve. Renal allograft biopsy is a helpful tool for determining the cause of graft dysfunction and adjusting patient management. Methods: Patients who received kidney transplantation and underwent allograft biopsy in Istinye University Hospital between January 2017 and January 2023 constituted the target population of this study. Demographic parameters, clinical data and biopsy indications, and histopathological assessment results of the patients were retrospectively analyzed. Results: Overall, 74 patients were included. The histopathology results included acute T-Cell mediated rejection (TCMR) (n = 15, 20%), tubular atrophy/chronic allograft nephropathy (IFTA) (n = 11, 15%), calcineurin inhibitor (CNI) toxicity (n = 2, 3%), chronic antibody-mediated rejection (ABMR) (n = 2, 3%), borderline pathology (n = 10, 13.5%), normal histology (n = 5, 6.5%), transplant glomerulopathy (TG) (n = 5, 6.5%), acute ABMR (n = 4, 5%), acute tubular necrosis (n = 7, 9%), polyomavirus nephropathy (n = 3, 4%) and non-specific changes (n = 10, 13.5%). The C4d was positive in 12% (n = 9) of the graft biopsies. In 73% (n = 54) of cases, the treatment strategy was changed based on biopsy results. Among all patients, 19 (25.6%) lost their grafts during follow-up. Conclusions: According to the histopathological analysis results, acute TCMR, IFTA, and borderline pathology were the most common causes of renal graft dysfunction. Renal allograft biopsy led to a remarkable change in treatment strategies in a significant number of cases.